Rapid Response to Experimental Warming of a Microbial Community Inhabiting High Arctic Patterned Ground Soil - Kevin K. Newsham; Birgitte Kortegaard Danielsen; Elisabeth Machteld Biersma; Bo Elberling; Guy Hillyard; Priyanka Kumari; Anders Priemé; Cheolwoon Woo; Naomichi Yamamoto (Biology, 2022)
The influence of climate change on microbial communities inhabiting the sparsely vegetated patterned ground soils that are widespread across the High Arctic is poorly understood. Here, in a four-year experiment on Svalbard, we warmed patterned ground soil with open top chambers and biannually irrigated the soil to predict the responses of its microbial community to rising temperatures and precipitation. A 1 °C rise in summertime soil temperature caused 44% and 78% increases in CO2 efflux and CH4 consumption, respectively, and a 32% increase in the frequency of bacterial 16S ribosomal RNA genes. Bacterial alpha diversity was unaffected by the treatments, but, of the 40 most frequent bacterial taxa, warming caused 44–45% reductions in the relative abundances of a Sphingomonas sp. and Ferruginibacter sp. and 33–91% increases in those of a Phenylobacterium sp. and a member of the Acetobacteraceae. Warming did not influence the frequency of fungal internal transcribed spacer 2 copies, and irrigation had no effects on the measured variables. Our study suggests rapid changes to the activities and abundances of microbes, and particularly bacteria, in High Arctic patterned ground soils as they warm. At current rates of soil warming on Svalbard (0.8 °C per decade), we anticipate that similar effects to those reported here will manifest themselves in the natural environment by approximately the mid 2030s.